Effectiveness of eco-feedback in improving the indoor air quality in residential buildings: Mitigation of the exposure to airborne particles. (December 2022) - Caracci, E.; Canale, L.; Buonanno, G.; Stabile, L.
Abstract: Indoor air quality, a major concern for human health, is strongly influenced by occupants' behavior but people are not aware about how their everyday behavior affects their exposure to pollutants. In the present paper we tried to cope with the gap of knowledge between lack of awareness and the understanding of how occupants' behaviors affect the environment. To this end we performed an evaluation of the IAQ awareness of 100 families through questionnaire surveys and an investigation of an "eco-feedback" strategy based on awareness-raising campaigns. In particular, information and experimental campaigns were conducted in 10 homes allowing the evaluation of its effectiveness in the short-term. Results showed that the occupants are not properly aware of the IAQ in their homes and of their exposure to airborne particles including the possible contribution of indoor sources. Anyway, the eco-feedback strategy adopted resulted successful both in terms of promoting behavioral changes of the occupants and reducing the concentration levels while airborne particle emitting sources (i.e. cooking) were in operation. Indeed, the exposure to airborne particles while cooking measured after the information campaign resulted lower than the baseline exposure with median relative reductions of 47% and 59% for PM10 and particle number concentration, respectively. The outcomes of the study could be of great interest for scientists involved in designing eco-feedback campaigns and indoor airborne particle monitoring since, for the first time, the potential effect of an eco-feedback strategy on indoor air quality was shown. Highlights: Population resulted not properly aware of the IAQ in their homes. An eco-feedback strategy based on information and experimental campaigns was adopted. The eco-feedback strategy resulted successful in promoting behavioural changes. The eco-feedback strategy adopted reduced the indoor particle concentrations. relative reductions of 47% and 59% were obtained for PM10 and PNC while cooking.